Elaboração e validação de uma EPA (Entrustable Professional Activities) sobre fratura da extremidade distal do rádio - Romanelli, Luciano Ramos (2020)
Introduction: The competency-based curriculum in postgraduate medical education has been adopted in many countries for years. However, whenever assessing a competency one must take into account which skill domains and the context it refers to. The Entrustable Professional Activities (EPA) is a tool that enables the assessment of the acquisition of skills for proper medical practice. Objectives: To elaborate and validate an EPA for the surgical treatment of the distal radius fracture at the Orthopedics and Traumatology Medical Residency at the São Francisco de Assis Hospital Complex. Methods: A list of surgical steps was created, observing the treatment of this type of fracture performed by specialists. Using the Delphi methodology in its electronic format, this list has been refined according to the opinion of 20 experts. The final questionnaire was applied to first, second and third year residents of the São Francisco de Assis Hospital Complex. The average of the grades obtained and the percentage of items achieved from the EPA were compared according to the course year. Student's t-test and analysis of variance were used to compare the averages and Cronbach's alpha test to evaluate the internal consistency of the EPA. Results: It took three rounds to reach consensus in the first phase. The final questionnaire contained 27 items divided into preoperative, intraoperative and postoperative procedures. In the second phase of the study, the questionnaire was administered to 23 resident physicians between September 2nd and October 4th, 2019, involving a total of 73 surgeries, with an average of 3.2 per resident. Virtually in all EPA items the obtained averages by the third-year residents were higher than those of the second and first years and the grades of second-year residents were higher than those of the first. These differences were statistically significant. The internal consistency was very high according to Cronbach's alpha. Conclusions: The EPA was successfully developed devising a tool that was capable of discriminating the resident physicians according to the year of residency